Analyzing Current Fetus Risk Conditions Through Fetal Heart Rate (FHR) and Uterine Constructions (UC) Values by Using Machine Learning Algorithms - Rafieipour, Moslem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Fetal Heart Rate (FHR) is often used to assess situation of fetal health. The aim of this thesis is to infer current fetus risk conditions by monitoring and computing FHR and Uterine Constructions (UC) values. Doppler devices are generally used for gathering FHR and UC values from labors instantly. Doppler devices produce Non-Stress Test (NST) graphs. In this thesis, we used the CTU-UHB intrapartum Cardiotocography database (CTU) which is gathered by Prague and Brno University Hospital (UHB). The database contains 552 Cardiotocography records (CTG) and each record involves a FHR and an UC signal. In this thesis, several machine learning algorithms are developed to perform feature extractions and classification to analyze NST graphs. MATLAB and R tools are used for signal processing, feature extraction and classification steps. With the proposed system, instant interpretation of FHR and UC signals on a NST records: (1) value of instant baseline, (2) variable baseline signal, (3) baseline variability, (4) type and number of accelerations, (5) type and number of decelerations, (6) classification of the NST traces. In experimental studies of this thesis, CTU-UHB Cardiotocography records are interpreted by an expert obstetrician. Experimental results are evaluated and compared with expert obstetrician’s observations and some of related works.

ÖZ: Fetal Kalp Hızı (FHR) genellikle fetal sağlık durumunu değerlendirmek için kullanılır. Bu tezin amacı FHR ve Uterus Kasılmaları (UC) değerlerini takip ve analiz ederek mevcut fetüsün anlık risk durumunu anlayan bir sistem önermektir. Doppler cihazları genellikle FHR ve UC sinyal değerlerini hamile bireylerden anlık toplamak için kullanılır. Doppler cihazları, test esnasında Stressiz Test (NST) grafikleri üretir. Bu tez çalışmasında, Prag Ve Brno Üniversite Hastanesi (UHB) tarafından toplanan CTU-UHB İntrapartum Kardiyotokografi Veri Tabanını (CTU) kullandık. Veri tabanı 552 Kardiyotokografi (CTG) kaydı içerir ve her kayıt bir FHR ve bir UC sinyali içerir. Bu tez çalışmasında, NST grafiklerindeki FHR ve UC sinyallerini yorumlamak için özellik çıkarımları ve sınıflandırma yapmak üzere birkaç makine öğrenme algoritması geliştirilmiştir. Geliştirme esnasında, MATLAB ve R yazılımları, sinyal işlemede, öznitelik çıkarımlarında ve sınıflandırma adımlarında kullanılmıştır. Önerilen sistem ile, FHR ve UC sinyalleri anlık yorumlanarak: (1) anlık temel/ortalama değeri, (2) değişken temel/ortalama değeri, (3) temel değişkenlik, (4) akselerasyon sayısı ve türleri, (5) deselerasyon sayısı ve türleri, (6) yukarıdaki ara çıktı sonuçları kullanarak, bebeğin anlık durum sonucu tanımlanır. Bu tezin deneysel çalışmalarında, CTU-UHB Kardiyotokografi veri setindeki kayıtlar, uzman bir kadın doğum doktoru tarafından yorumlanmıştır. Deneysel sonuçlar, uzman kadın doğum doktorunun sonuçları ve ilgili bazı çalışmaların sonuçları ile değerlendirilmiş ve karşılaştırılmıştır.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2019. Supervisor: Assoc. Prof. Dr. Duygu Çelik Ertuğrul.
Keywords: Computer Engineering Department; Fetal Heart Rate--Data processing Artificial intelligence--Medical applications Image Processing, Computer-Assisted Optical data processing Medical informatics--Computational intelligence; Fetal Heart Rate, Uterine Contraction, Machine Learning, Doppler, NST, Cardiotocography